Fuzzy p-absolutely summable difference sequences - Dutta, Hemen; Kilicman, Adem; Esi, Ayhan (World Scientific Publishing, 2018)
In this work, we introduce the notion of p-absolutely summability of difference sequences of fuzzy numbers and then reduce the concept of p-absolutely summable sequences of fuzzy numbers. We discuss the sets of such sequences of fuzzy numbers under different fuzzy metrics. We also establish the completeness under suitable metric. Examples along with suitable explanation are incorporated to make the theory of this paper interesting and useful. Finally, the concepts of fuzzy solidity and fuzzy symmetricity are defined and the classes for these two properties are examined as well.